Views from midwives and perinatal nurses on barriers and facilitators in responding to perinatal intimate partner violence in Japan: baseline interview before intervention - Naoko Maruyama; Shigeko Horiuchi (BMC, 2024)
Abstract Background Midwives and perinatal nurses play a crucial role in responding to intimate partner violence (IPV) against pregnant women; however, these roles are often not performed adequately. This study aimed to identify provider-related, healthcare system, and social barriers and facilitators to IPV response from the perspective of midwives and perinatal nurses. Methods This qualitative descriptive study used semi-structured interviews with five midwives and a nurse from perinatal care facilities in Tokyo, Japan. A framework approach was employed to analyze the interview transcripts. Results Barriers included inadequate knowledge about IPV and reluctance to provide support by healthcare providers. Barriers in the healthcare system included the absence of structural infrastructure for IPV response. This involved the lack of screening tool adoption, the partner's presence during interviews, and time constraints. Additionally, there was insufficient systematic and collaborative coordination within and outside the team. Another barrier was the lack of in-service training to develop IPV-related knowledge and skills. Finally, there was uncertainty about how the support at healthcare facilities impacts women's lives. Further barriers in the social system included the absence of additional reimbursement for IPV response. There was also a lack of a comprehensive approach to IPV that provides for the rehabilitation of perpetrators and care for the children of victims and a culture that discourages separation from the perpetrator. Conversely, facilitators included healthcare providers recognizing the perinatal period as an opportunity to address IPV. They also acknowledged IPV as a prevalent issue, practiced conscious self-care, and systematically collaborated within the healthcare team. Conclusion This study emphasized the need for routine IPV screening in perinatal care and the importance of team-based educational interventions for healthcare providers to facilitate implementation.